Prediction of the macroscopic mechanical properties of carbonate from nano-indentation tests - Vialle, Stephanie; Pazdniakou, A.; Adler, P. (2018)
Copyright © 2018 ARMA, American Rock Mechanics Association. The nano-indentation technique was applied to microporous carbonates from the Easter Parisian Basin made of nearly 100% calcite. Room-dried, small, irregular pieces, 5mm thick and with a polished surface of about 1 cm2 are used. Then, the distribution function and the linear auto-correlation of the indentation modulus are derived from these data. The numerical analysis consists in generating random three dimensional media with a local indentation modulus M(x) which has the same statistical properties as the measured ones. This is achieved via a non linear transformation of normal correlated Gaussian fields. Then, the elasticity equation with variable Lamé coefficients is solved by a code based on lattice springs. The elastic velocities are derived and compared to the measured ones.